Phytochemistry in the Ethnopharmacology of North and Central America - Arnason, John Thor; Harris, Cory S.; Guerrero-Analco, José A. (Frontiers in Pharmacology, 2022)
Traditionally the role of phytochemistry in the ethnopharmacology of North and Central America has been to characterize plant materials so that they can be produced reproducibly for commercial use or to identify active principles in unstudied traditional medicines for drug discovery. With new decolonial objectives coming from Indigenous communities, emphasis has shifted to evaluating the safety and efficacy of traditional medicines and preparations for community use. With new techniques and technologies available, scientific focus has shifted from individual bioactives to more rapid and comprehensive chemical characterizations and polypharmacy of traditional medicines. Untargeted metabolomics and associated statistical treatments have greatly expanded identification of components, improved species and cultivar identification and provided means for identifying multiple activity biomarkers, via chemometric and biochemometric analysis. New integrated techniques are available for identifying multiple active principles and synergists. The recent explosion of information is not without problems that need to be addressed including many unconfirmed tentative identifications of phytochemicals, lack of quantitative testing, superficial chemical activity testing and continuing need for dereplication.